(untitled) - Brown, James Dean (Upper Saddle River, 2005)
"Testing in Language Programs" is a comprehensive text for teachers and students in teacher-training courses in language testing and assessment. Ideal for both classroom use and personal reference, this book targets the needs of those making both programme-level (e.g. admissions, proficiency and placement) as well as classroom-level testing decisions (e.g. assessing what students have learned through diagnostic and achievement testing).
Keywords: Examinations,Examinations,Language arts; Design and construction,Validity,Ability testing